Dual adsorbent-photocatalytic Keratin-TiO 2 photocatalytic nanocomposite for trimethoprim removal from wastewater - Villanueva, María Emilia (2020)
Trimethoprim is an emerging pollutant that has been found in ground water in alarming concentrations. Thus, the development of economical and efficient advanced water treatment technologies is crucially needed. In this paper, a keratin hydrogel with immersed TiO2 nanoparticles (nTiO2) was developed. The material was characterized by using FT-IR and FT-Raman spectroscopies that showed that a physical interaction between nTiO2 and the keratin hydrogel took place. Dielectric spectroscopy confirmed the influence of this interaction on the keratin structure. Swelling studies showed that it depended on the medium pH, being higher at basic pH values. Photocurrent measurements revealed an enhanced photocurrent of the hydrogels, which may be due to the improved transport of the photogenerated carriers via the porous network structure. The model pollutant was trimethoprim, an emerging pollutant. These hydrogels showed the ability to adsorb and degrade trimethoprim in the presence of simulated solar light under batch conditions for at least four cycles with no significant decrease in efficiency. Experimental variables (time, temperature, and pH) were studied in order to characterize the material adsorption and photodegradation performance, concluding that temperature is the main variable to consider in the adsorption process.